PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE CUBOS DE CAFÉ GOURMET INSTANTANEO ENDULZADOS CON PANELA ORGÁNICA EN LA CIUDAD DE LOJA - LÓPEZ FAICÁN, TATIANA MARICELA (2016)
The developed investigation refers to a project of feasibility, for the implementation of a production company and commercialization of cubes of instantaneous brown gourmet sweetened with organic panela in the City of Loja. The investigation was carried out by means of consultations to several sources like primary and secondary, the obtained information, by means of surveys and interviews carried out to the Families of the City of Loja, in a total of 400 interviewed families, of those which 58,08% that corresponds to a 19.645 families are possible plaintiffs, with a consumption average of 8.545.469 units of annual cubes of coffee, of those which the company "Proena" will cover 16% that corresponds at 1'386.048,00 annual cubes of coffee to take place. In the technical study, it is pointed out that this company, it will be located in the County of Loja, specifically in the City of Loja, neighborhood Time, street Colombia between Brazil and Philippines. As for the lifespan of the project it is of 5 years, the unitary cost is 0,11 $, with 45% of utility and with a selling price to the public of 0,16 $, and the box of 24 units has a price of $3,84 for the commercialization of these products, the Producing channel was used - Distributor. Consumer. The investment of the project ascends to 71.334, 38 dollars, the one that will be paid with 30% of own capital that corresponds to 21.400,31 dollars and 70% obtained by means of credit that means 49.934,07 dollars. Inside the Financial Evaluation, it was determined that the project if it is feasible according to the economic indexes as they are: the Current Net (VAN) Value, with the quantity of 145.943,42 dollars; It appraises it Interns of Return of 74%; Relationship Benefits Cost of $ 1,46 forty six cents for 5 invested dollar; Period of Recovery of Capital 3 years old, 5 month, 15 days and 0 hours, Analysis of Sensibility of the 0,86, with increment of the costs of 8%; and with decrease of 6% in the revenues, with sensibility of 0,85%. For the correct operation of the company, it has felt convenient to require of: the personnel that was hired, manager, advisory juridical, secretary, accountant, production boss, boss of sales, workers, salesperson, and driver. And to conclude the microempresa, it will be conformed according to the norms that it establishes the Limited company, with their respective flowcharts, structural, functional, posicional, manual of functions.